Original Intent, History, and Doctrine: The Constitution and Economic Liberty - Scheiber, Harry N. (American Economic Review, 1988)
One of the enduring and truly perplexing issues in American legal theory is the question of how and to what degree the values associated with are embodied in the United States Constitution. Recent controversies, both in law and in economics, on the efficiency of the public sector in regulation and in the provision of public goods, on the virtues or perils of privatization, and on public choice and the legal process proceed too often without reference to the American system's constitutional heritage. The assumptions often manifest in neoconservative analysis, particularly the view that economic liberty